1985
DOI: 10.1063/1.336177
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of planar rf discharges for dry etching

Abstract: rf impedance, dc self-bias, and ion sheath (dark space) thicknesses are measured in an O2 discharge for 7–53 Pa pressure and 50–800 W rf power (13.56 MHz). Special attention is paid to corrections for reactor stray impedances. It is concluded that the discharge can be described as a capacitance (the ion sheath) with both a parallel and a series resistance, the series element being the more important one. Good agreement is found between optical and electrical measurements of the ion sheath thickness. Evidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 15 publications
2
26
0
1
Order By: Relevance
“…The experimental data we obtained for T e are in good agreement with the calculations from [37]. At the same time we observed an additional brightly shining layer inside the nearelectrode sheath of the RF discharge in electronegative gases SF 6 and CF 4 . However, the probe measurements in these gases are impeded, because the surface of the probe is quickly coated with a sulphur film (in SF 6 ) or a polymer film in CF 4 , which are difficult to remove simply by heating the probe to a high temperature.…”
Section: Article In Presssupporting
confidence: 80%
See 3 more Smart Citations
“…The experimental data we obtained for T e are in good agreement with the calculations from [37]. At the same time we observed an additional brightly shining layer inside the nearelectrode sheath of the RF discharge in electronegative gases SF 6 and CF 4 . However, the probe measurements in these gases are impeded, because the surface of the probe is quickly coated with a sulphur film (in SF 6 ) or a polymer film in CF 4 , which are difficult to remove simply by heating the probe to a high temperature.…”
Section: Article In Presssupporting
confidence: 80%
“…Van Roosmalen et al [6] carried out experiments in 13.56 MHz oxygen discharge at 6.67-53.3 Pa and 50-800 W. They attempted to reconcile their experimental results with various theoretical models and found that more than half the dissipated power remains physically unaccounted for. Jurgensen [7] proposed a model of the near-electrode sheath of the RF discharge in oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing pressure decreases electron diffusion toward the electrode because of an increase in electron-neutral collisions, so the DC self-bias voltage also decreases as the pressure increases [19]. The sheath thickness and DC self-bias voltage were found to decrease with increasing pressure at 53-400 mTorr [24] and 20-200 mTorr [25]. The measurements showed that the capacitive reactance of the sheath decreased at higher pressures.…”
Section: Self-bias Voltage Regression Modelmentioning
confidence: 73%